A detailed mapping of the food industry in the European single market: similarities and differences in market structure across countries and sectors - Iris Van Dam; Benjamin Wood; Gary Sacks; Olivier Allais; Stefanie Vandevijvere (BMC, 2021)
Abstract Background Food environments are influenced by food industries (packaged food and non-alcoholic beverage manufacturers; supermarkets and quick service restaurants). An important source of this influence is the significant market power held by a limited number of food companies. Market structure analysis, as part of a broader market power research agenda, has received limited attention from the public health community. The aim of this study was to analyse similarities and differences in market structure across countries and industries in the European Single Market. Methods The companies with the largest market share at the national level for each industry were identified from Euromonitor sales data in 2017/18. The market structure was assessed by the following metrics: the number of global brand owners with ≥1% market share per country, the number of companies unique for one European Single Market member state, the most sold packaged food and non-alcoholic beverage categories, the number of quick-service restaurants and supermarkets per 1000 inhabitants and market concentration by means of the Herfindahl-Hirschman Index (HHI) and the four firm concentration ratio (CR4). CR4-values > 40% and HHI-values > 2000 indicate concentrated markets with limited competition. Results The leading packaged food and non-alcoholic beverage manufacturers and the most sold food and beverage product categories were similar across countries in Europe. The observed levels of concentration were however different. Average CR4-values ranged from 21 to 72% among packaged food product markets and 60 to 76% for non-alcoholic beverage product markets. Average CR4-values for quick service restaurants and supermarkets were 50 and 60%, respectively. Across European countries the same leading quick-service restaurants were identified, while this was not the case for supermarkets. Conclusions This study forms an important basis to understand key aspects of market structure of the European food industry, observing clear differences between food industries and European Single Market member states. This has potential implications for the implementation of food environment policies at different levels of jurisdiction.